(untitled) (Research, Society and Development, 2019)
Children are increasingly getting removed from mediums that allow for the development of their many abilities, and the lack of environments that are attractive for them within the urbanspace is one of the contributing factors. The objective of this research is to discuss how public places can contribute to child development, through the use of the urban space and bigger interaction within the environment they live in, proposing the increase of the access and the occupation of public spaces. For this purpose, the used methodology was a non-systematic bibliographic review, from a perspective based on the works of Lev Vygotsky and Urie Bronfenbrenner’s Ecological Theory. It was concluded that it is necessary not only that the access to these spaces be broaden, but that they be suited for children’s use in a way that stimulates their full development, providing well-being and quality of life.